La conciencia regional en España / José Jiménez Blanco (director) ; Manuel García Ferrando y Eduardo López-Aranguren (subdirectores) ; Miguel Beltrán Villalba - García Ferrando, Manuel (1942-) Jiménez Blanco, José (1930-2009) López Aranguren, Eduardo MaríaBeltrán, Miguel (1935-) (Colección Monografías; 3)
Incluye anejo con el modelo de cuestionario utilizado en el estudio